VOCABULARY TO YOUNG LEARNERS VERBAL AND WITH ACTION - Sultonova Nodirabonu Rustamjon qizi (Journal of new century innovations, 2022)
Annotation: In this article, discusses how to teach verbal and with action vocabulary to young learners, and other additional information is also mentioned.